The Role of The LCGC (Low Cost Great Curriculum) Model on Teacher Performance in The Implementation of The Independent Curriculum - Muchtar, Azmy Ali; Marhamah, Marhamah; Puadah, Popi (Jurnal Paedagogy, 2025)
This study aims to analyze the role of the LCGC (low cost great curriculum) model on teacher performance in implementing the Merdeka curriculum in Madrasah. This study used a quantitative approach with an associative correlational design. The study population consisted of all Madrasah teachers in DKI Jakarta, with a sample of 40 participants taken using a purposive sampling technique from two madrasah, namely Madrasah Nur-Attaqwa and Madrasah Ar-Rahmah. The measuring instrument used was the LCGC Model scale adapted from the Charles O. Jones policy implementation model and the Ornstein and Hunkins Curriculum Implementation model: (Modernism and Postmodernism). The data obtained were analyzed using a simple regression test. The results of this study indicate a significant positive relationship between the implementation of the LCGC Model and teacher performance in implementing the Merdeka Curriculum, with a Pearson correlation value of 0.947. This study also identified the challenges faced by teachers, such as understanding and skills in innovative learning methods, as well as the importance of support from parents and the community.